2019
DOI: 10.1016/j.celrep.2019.04.036
|View full text |Cite
|
Sign up to set email alerts
|

CYLD Regulates Centriolar Satellites Proteostasis by Counteracting the E3 Ligase MIB1

Abstract: Graphical AbstractHighlights d A subset of CYLD is found at the centriolar satellites d CYLD maintains the proteostasis of the centriolar satellites d CYLD removes ubiquitin chains bound to the E3 ligase MIB1 d CYLD counteracts MIB1-mediated disruption of the centriolar satellites SUMMARYThe tumor suppressor CYLD is a deubiquitinating enzyme that removes non-degradative ubiquitin linkages bound to a variety of signal transduction adaptors. CYLD participates in the formation of primary cilia, a microtubule-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…Cylindromatosis (CYLD) is a member of the USP family of proteins and is expressed in centriolar satellites [ 148 ]. CYLD stimulates ciliogenesis by stabilizing centrosomal protein 70 (CEP70) and pericentriolar material 1 (PCM1) [ 132 , 133 ]. Stabilization of PCM1 by CYLD is mediated by deubiquitination of mindbomb E3 ubiquitin protein ligase 1 (MIB1), which is activated by ubiquitination on lysine 63 [ 133 ].…”
Section: Roles Of E3 Ubiquitin Ligases and Dubs In Ciliogenesis Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Cylindromatosis (CYLD) is a member of the USP family of proteins and is expressed in centriolar satellites [ 148 ]. CYLD stimulates ciliogenesis by stabilizing centrosomal protein 70 (CEP70) and pericentriolar material 1 (PCM1) [ 132 , 133 ]. Stabilization of PCM1 by CYLD is mediated by deubiquitination of mindbomb E3 ubiquitin protein ligase 1 (MIB1), which is activated by ubiquitination on lysine 63 [ 133 ].…”
Section: Roles Of E3 Ubiquitin Ligases and Dubs In Ciliogenesis Cmentioning
confidence: 99%
“…CYLD stimulates ciliogenesis by stabilizing centrosomal protein 70 (CEP70) and pericentriolar material 1 (PCM1) [ 132 , 133 ]. Stabilization of PCM1 by CYLD is mediated by deubiquitination of mindbomb E3 ubiquitin protein ligase 1 (MIB1), which is activated by ubiquitination on lysine 63 [ 133 ]. Lysine 63-ubiquitinated MIB1 then ubiquitinates PCM1 and stimulates its degradation in proteasomes.…”
Section: Roles Of E3 Ubiquitin Ligases and Dubs In Ciliogenesis Cmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Gao et al identified that, Cyld interacts with tubulins, and the activity of this DUB is required for microtubule assembly and maintaining its stability. Consequently, it is possible that Cyld is also necessary for several autophagic processes, which use vesicular trafficking mechanisms [ 83 , 97 , 98 , 99 , 100 ].…”
Section: The Activity Of Deubiquitinating Enzymes In Autophagic Mementioning
confidence: 99%